Clinical and serological comparison of 17 chronic progressive systemic sclerosis (PSS) and 17 CREST syndrome patients matched for sex, age, and disease duration. Issue 6 (December 1984) - Furst, D E; Clements, P J; Saab, M; Sterz, M G; Paulus, H E
Abstract : This study compares the clinical and serological differences between 17 PSS and 17 carefully matched CREST patients. Patients were matched for sex, age by decade, and, importantly, disease duration (11.2 +/- 9.2 vs. 12.0 +/- 9.3 years). Muscular and skin involvement were greater for the PSS groups (p less than 0.02) and pulmonary involvement was also greater (p less than 0.05), at least for non-smoking PSS patients. On the other hand no clinically significant differences were found between groups for other visceral involvement--including comparisons of gastrointestinal, cardiovascular, and renal involvement. There were also no laboratory differences except in anti-RNP antibody (p less than 0.04).